Fracture of refractories at room and elevated temperatures analyzed with wedge splitting tests and image correlation - Maginador, Rafael Vargas (2024)
Industrial high-temperature processes relies on castable refractories, whose formulation and characterization become crucial for minimizing energy loss and costs. Increasing the failure predictability is key to reducing risks in such applications. Few high-temperature mechanical tests were analyzed with full-field measurement techniques that allow for the evaluation of fracture mechanisms directly for in-service temperature ranges. With complex microstructures, crack propagation is not always known through the depth of the specimen. This thesis aims to fill in this gap with the analysis of full-field measurements of Wedge Splitting Tests (WSTs) under two experimental configurations, namely, high-temperatures assisted by Digital Image Correlation (DIC), and room-temperature WSTs performed within a tomograph with Digital Volume Correlation (DVC). Experimental forces and full-field displacements provide trustworthy boundary conditions and robust data to validate simulations of crack propagation with Finite Element (FE) codes. Two furnaces suited for DIC were used for the thermomechanical experiments, one reaching up to 600°C and another, built during this thesis, up to 900°C, with the former allowing for the visualization from one side and the latter from opposite sides of the sample. An alumina-based castable refractory with mullite-zirconia aggregates was used for the studies, providing technologically relevant toughening at higher temperatures and good contrast for X-ray imaging. Cohesive zone models were chosen to describe crack propagation, whose parameters were calibrated using the FE Model Updating (FEMU) technique. Several methodological developments were needed from exploiting a limited field-of-view, design and fabricating one furnace, to using additive manufacturing to produce molds for notched cylindrical specimens. Fracture parameters were obtained in different configurations, and are discussed considering changes arising from the specimen geometry, crack path definition, sintering and testing temperatures. Insight is given into fracture processes in this stable crack propagation test within the bulk of the specimen and in environments closer to the final application temperatures.